Evaluating the effectiveness of the implementation of financial and investment strategies of industrial enterprise - Lytvyn, Inna (My University, 2023)
The article examines the effectiveness of implementing financial and investment strategies in industrial enterprises, emphasizing the need for multi-level evaluation tools in a rapidly changing economic environment. The study highlights that the implementation of financial and investment strategies is directly influenced by external market dynamics, technological shifts, and organizational capabilities. The author systematizes existing scientific approaches to evaluating enterprise development and argues that traditional assessment models—based solely on financial indicators or integrated indexes—are insufficient for modern industrial enterprises. Special attention is given to the specifics of agricultural machine-building enterprises, whose development depends not only on internal efficiency but also on external factors such as access to financial resources, market fluctuations, and innovation adoption. The article stresses the importance of linking enterprise development indicators with the indicators of financial management effectiveness and adjusting such evaluations to reflect positive or negative environmental influences. This system is closely connected with enterprise development management processes and supports continuous improvement of financial decision-making. The multi-indicator approach ensures a more accurate assessment of strategic financial management, enabling enterprises to identify development reserves and optimize financial support mechanisms. У статті розглядається ефективність впровадження фінансових та інвестиційних стратегій на промислових підприємствах, підкреслюючи необхідність багаторівневих інструментів оцінки в умовах швидкозмінного економічного середовища. У дослідженні підкреслюється, що на впровадження фінансових та інвестиційних стратегій безпосередньо впливають динаміка зовнішнього ринку, технологічні зрушення та організаційні можливості. Автор систематизує існуючі наукові підходи до оцінки розвитку підприємств та стверджує, що традиційні моделі оцінки, засновані виключно на фінансових показниках або інтегрованих індексах, є недостатніми для сучасних промислових підприємств. Особлива увага приділяється специфіці підприємств сільськогосподарського машинобудування, розвиток яких залежить не лише від внутрішньої ефективності, а й від зовнішніх факторів, таких як доступ до фінансових ресурсів, коливання ринку та впровадження інновацій. У статті наголошується на важливості пов'язування показників розвитку підприємств з показниками ефективності фінансового менеджменту та коригування таких оцінок з урахуванням позитивного чи негативного впливу навколишнього середовища. Ця система тісно пов'язана з процесами управління розвитком підприємств та підтримує постійне вдосконалення прийняття фінансових рішень. Багатоіндикаторний підхід забезпечує точнішу оцінку стратегічного фінансового менеджменту, дозволяючи підприємствам виявляти резерви розвитку та оптимізувати механізми фінансової підтримки.
Keywords: кафедра міжнародної економіки; investment strategy; industrial enterprise; development management; evaluation system; фінансова підтримка; фінансова архітектура; фінансова архітектура; інвестиційна стратегія; промислове підприємство; управління розвитком; система оцінювання; система оцінювання